2013
DOI: 10.5812/cardiovascmed.8051
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of aortic regurgitation following percutaneous mitral valvuloplasty

Abstract: Background:Little is known about the natural history of aortic regurgitation (AR) in patients undergoing mitral valve procedures for mitral stenosis.Objectives:The aim of this study was to evaluate the short- and long-term effects of percutaneous mitral valvuloplasty (PMV) on coexisting AR.Materials and Methods:A total of 327 patients with rheumatic mitral stenosis (282 females and 45 males; mean age at the time of intervention = 47 ± 11 years) were followed up for between 48 hours and 13 years after PMV. At t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
(22 reference statements)
1
2
0
Order By: Relevance
“…During the course of our study the slow progression of AR was in accordance with available natural history studies on the same condition [16,18,23,33].…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…During the course of our study the slow progression of AR was in accordance with available natural history studies on the same condition [16,18,23,33].…”
Section: Discussionsupporting
confidence: 66%
“…In this condition, it might be expected that AR would progress rapidly. However, various studies found that patients with mild AR at the time of mitral valve procedures (Surgery or mitral balloon valvuloplasty) rarely develop severe AR [17][18][19][20][21][22][23] In recent study, Namboodiri and colleagues [16] found that mild AR progressed very slowly and less frequently required reintervention ,but mild aortic stenosis (AS) progressed more often and more rapidly. In Chaouch's study [17] 38% of patients who had mild AS required aortic valve replacement during mean follow-up of 5 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation